Parasitoid wasps (Ichneumonoidea) collected from faba bean fields, Kharga Oasis, New Valley, Egypt, with new records and the description of a new species - Gadallah, Neveen S.; Edmardash, Yusuf A.; Mansour, Amany N.; Imam, Ahmed I. (Zootaxa, 2023)
A faunistic inventory of ichneumonoid wasps collected from faba bean fields (Vicia faba L.) in Kharga Oasis, New Valley, Egypt is presented. Fourteen species of Braconidae in 11 genera and five subfamilies (Aphidiinae, Braconinae, Euphorinae, Microgastrinae, and Opiinae); and six ichneumonid species in five genera and three subfamilies (Campopleginae, Diplazontinae, and Ichneumoninae) were collected and identified. Among those, three genera Barichneumon Thomson, and Virgichneumon Heinrich (Ichneumoninae, Ichneumonidae), and Centistes Haliday (Euphorinae, Braconidae), and five species: Cotesia icipe Fernández & Fiaboe, 2017 (Microgastrinae) (Braconidae), Diadegma trochanteratum (Thomson, 1887), and Sinophorus tibialis Sanborne, 1984 (Campopleginae), Barichneumon bilunulatus (Gravenhorst, 1829), and Virgichneumon callicerus (Gravenhorst, 1820) (Ichneumoninae, Ichneumonidae) are new records to the Egyptian fauna. A new species, Trioxys khargaiensis Gadallah & Edmardash (Aphidiinae: Braconidae) is described and illustrated. A faunistic list comprising diagnostic characters and distribution in the Middle East and North Africa is provided. Illustrations of species’ characters are also provided.